A effective DNA vaccine against diverse genotype J infectious hematopoietic necrosis virus strains prevalent in China. Issue 18 (25th April 2017) - Xu, Liming; Zhao, Jingzhuang; Liu, Miao; Kurath, Gael; Ren, Guangming; Lapatra, Scott E.; Yin, Jiasheng; Liu, Hongbai; Feng, Jian; Lu, Tongyan
Highlights: An effective DNA vaccine was constructed by using glycoprotein of a J genotype IHNV strain. The DNA vaccine was efficient to IHNV strains from different geographic locations in China. A single 100 ng dose of the DNA vaccine could provide significant protection to rainbow trout. The significant protection could be induced at 4 days post vaccination and lasted 180 days. Abstract: Infectious hematopoietic necrosis virus (IHNV) is the most important pathogen threatening the aquaculture of salmonid fish in China. In this study, a DNA vaccine, designated pIHNch-G, was constructed with the glycoprotein (G) gene of a Chinese IHNV isolate SD-12 (also called Sn1203) of genotype J. The minimal dose of vaccine required, the expression of the Mx-1 gene in the muscle (vaccine delivery site) and anterior kidney, and the titers of the neutralizing antibodies produced were used to evaluate the vaccine efficacy. To assess the potential utility of the vaccine in controlling IHNV throughout China, the cross protective efficacy of the vaccine was determined by challenging fish with a broad range of IHNV strains from different geographic locations in China. A single 100 ng dose of the vaccine conferred almost full protection to rainbow trout fry (3 g) against waterborne or intraperitoneal injection challenge with IHNV strain SD-12 as early as 4 days post-vaccination (d.p.v.), and significant protection was still observed at 180 d.p.v. Intragenogroup challenges showed that the DNA vaccine provided similar protection to the fish against all the Chinese IHNV isolates tested, suggesting that the vaccine can be widely used in China. Mx-1 gene expression was significantly upregulated in the muscle tissue (vaccine delivery site) and anterior kidney in the vaccinated rainbow trout at both 4 and 7 d.p.v. Similar levels of neutralizing antibodies were determined with each of the Chinese IHNV strains at 60 and 180 d.p.v. This DNA vaccine should play an important role in the control of IHN in China.